Comparing stakeholder perceptions with empirical outcomes from negotiated rulemaking policies: Is participant satisfaction a proxy for policy success?. (November 2016) - McDonald, Sara L.; Lewison, Rebecca L.; Roady, Stephen E.; Kramer, Randall A.; Rigling-Gallagher, Deborah; Read, Andrew J.
Abstract: Evaluation of natural resource management policies often is made difficult by lack of robust or long-term data on the resource. In the absence of empirical data, natural resource policy evaluation may rely on expert or stakeholder perception of success as a proxy, particularly in the context of policies that depend on multi-stakeholder engagement or negotiated rulemaking. However, few formal evaluations have compared empirical ecological outcomes with stakeholder perception. This study compares stakeholder perceptions of policy outcomes with ecological outcomes from a long-term, ecological dataset as part of the U.S. Marine Mammal Protection Act's Take Reduction Planning process. Structural Equation Models revealed that stakeholder perceptions were significantly and positively related to positive ecological outcomes. Also, perceived success and ecological performance rankings of the Take Reduction Plans were comparable for three of the five plans examined. This analysis suggests that for this particular policy instrument, stakeholder perception aligns well with ecological outcomes, and this positive relationship is likely the result of a commitment and support for stakeholder education and engagement. However, even within a single policy analysis, there was variability suggesting that the relationship between stakeholder perceptions and policy outcomes must continue to be evaluated. This study suggests that stakeholder perception can be an accurate reflection of ecological outcomes, but not necessarily a predictor of them. Highlights: Lack of robust, ecological data make it difficult to evaluate natural resource management policies. Natural resource policy evaluation may, thus, rely on stakeholder perception of success as a proxy for empirical success. We examined a long-term, ecological dataset as part of the Marine Mammal Protection Act's Take Reduction Planning process. Stakeholder perceptions of policy outcomes were then compared with ecological outcomes. Stakeholder perception can be an accurate reflection of ecological outcomes, but not necessarily a predictor of them.